PENERAPAN MODEL PEMBELAJARAN TGT BERBANTU JAM SUDUT DITINJAU DARI HASIL BELAJAR MATEMATIKA DI SEKOLAH DASAR - Lestari, Mukti; Sary, Ryky Mandar (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of this research is to determine the completeness of Mathematics learning outcomes at class III on Angle Material through TGT model learning assisted by Angle Clock Learning Media. The research method used is a quantitative method in the form of an experiment with a one group pretest-posttest design. The population in this study was class III students at SD Negeri 03 Cibelok in the academic year 2023/2024 with totaling 36 students. Data collection was obtained through the test method to determine student learning outcomes. Data were analyzed through the normality test, T-test, test for increasing learning outcomes (N- Gain test). The results of the research show that the learning outcomes of class III students at SD Negeri 03 Cibelok on Angle material after using the TGT Model assisted by Angle Clock have achieved learning completeness. It is known from the tcount>ttable value is 17,327 > 1,690. There is a significant difference on student learning outcomes after using TGT Assisted by Corner Clock Learning Media.